R&D infield of “Waste-to-Energy”in Institute of Raw Materials Preparation and Environmental Processing, University of Miskolc - Bokányi, Ljudmilla; Csőke, Barnabás; Gombkötő, Imre; Nagy, Sándor; Pintér-Móricz, Ákos (International Journal of Engineering and Management Sciences, 2018)
The importance of research and development in the field of „Waste-to-Energy” is vital in our modern society trying to establish the circular economy. Such R&D activity has been carrying out at Institute of Raw Materials Preparation and Environmental Processing for decades in several directions. This paper deals with the main results of research on refuse derived fuel from MSW, biogas production, briquetting of biomass, as well as production of fluid fuels.